BALAPAN LIAR DI KALANGAN REMAJA (STUDI KASUS PELAJAR SMP-SMA KELURAHAN SRI MERANTI KECAMATAN RUMBAI KOTA PEKANBARU) - Febry, Lismaharia; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Illegal racing is a race among motorcycle and also cars in a public road. This research aims to discover the factors and the impact which causes illegal racing by teenagers. The research using the theory of deviant behavior, juvenile delinquency and social control support by the books with a common discuss. The research method is qualitative descriptive with observed, interviews and documentation technique to take the result. This research subjects selected by accidental sampling which is based on coincidence or anyone around study site. As the final result of this research, the conclusion is teenagers do illegal racing with deviation patterns forming a juvenile delinquency.Keywords : Ilegal Racing, Juvenile, Juvenile Delinquency